Nutritive value of dried and heat processed mola fish (Amblypharyngodon mola) products (International Journal of Natural Sciences, 2012)
Sensory characteristics, nutritive and food qualities of traditional, rotary and solar tunnel dried mola (Amblypharyngodon mola) products were investigated. Nutritional analyses of fresh mola fish at various steps of heat processing (cooking) were also studied. Organoleptically, the colour of traditional dried mola products was slight brownish with emission of faint off odour. On the other hand, the colour of dried mola fish produced in rotary and solar tunnel dryer was showed characteristic shiny colour and whitish to slight brownish respectively. For traditional dried mola products texture was somewhat soft, whereas it was firm and flexible with characteristic fresh fishlike odour for rotary dryer and solar tunnel dryer. Traditionally dried products were not satisfactory and found to be infested. On the contrary, rotary and solar tunnel dried mola products were excellent having no insect infestation or broken pieces. The dried mola products showed different nutritional contents significantly (p